2010
DOI: 10.1007/s11325-010-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of snoring on microalbuminuria in diabetic patients

Abstract: Prevalence of OSA-related symptoms was very common in diabetic patients and further prospective studies are needed to elucidate the role of OSA's effect on diabetic control and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Indeed this has been shown to be the case for OSA (74). Further, snoring has been linked to microalbuminuria -a persistent increase in urinary albumin -an early indicator of diabetes nephropathy (75). Interestingly, one study showed increased prevalence of diabetes in habitual snorers compared to non-snorers in women but not in men, after controlling for BMI and waist circumference (76).…”
Section: Cardiovascular Andmentioning
confidence: 99%
“…Indeed this has been shown to be the case for OSA (74). Further, snoring has been linked to microalbuminuria -a persistent increase in urinary albumin -an early indicator of diabetes nephropathy (75). Interestingly, one study showed increased prevalence of diabetes in habitual snorers compared to non-snorers in women but not in men, after controlling for BMI and waist circumference (76).…”
Section: Cardiovascular Andmentioning
confidence: 99%
“…Based on earlier data identifying obstructive sleep apnea (OSA) and snoring as independent risks for developing insulin resistance [50], a group of investigators studied OSA as an independent risk factor for the development DN and microalbuminuria [51]. It included 237 type 2 diabetic patients, where 60.3% of patients suffered from snoring, while 31.6% complained of excessive daytime sleepiness [51].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…It included 237 type 2 diabetic patients, where 60.3% of patients suffered from snoring, while 31.6% complained of excessive daytime sleepiness [51]. Using both the Berlin Questionnaire [52] and past medical records, patients were classified as having either a high or low pre-test risk for OSA [51].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
See 2 more Smart Citations